THE IMPACT OF MARKETING MIX ON CUNSOMER SATISFACTION AND CUSTOMER LOYALTY ON AQUA PRODUCTS - hayuningtyas, primawati (Universitas Dr. Soetomo, 2020)
Almost every company in Indonesia carries out a variety of strategies to be competitive. In the Bottled Drinking Water Industry, the result of a research carried out by Mandiri Industry Update (2015) indicated the existence of intense competition, with more than 500 bottled water companies, of which 60% were mostly local players. This should be a concern for Danone Group with the AQUA brand that currently still dominates the market. AQUA must continue to maintain its market share by finding ways to provide satisfying products to costumers in order to encourage loyalty so that AQUA can survive in the competition. This study was chosen based on the researcher's interest in the effect of satisfaction felt by costumers on costumer loyalty to AQUA products. In this case, the Marketing Mix (product, price, place, promotion) forms the factors that lead to costumer satisfaction and loyalty (Wahab et al, 2016). This study was conducted in the campus environment of Airlangga University with as many as 80 students. The results of this study using empirical data indicated that the marketing mix variables consisting of product, price, promotion, place had a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on costumer loyalty.